Impact of myocardial fibrosis on left ventricular remodelling, recovery, and outcome after transcatheter aortic valve implantation in different haemodynamic subtypes of severe aortic stenosis. (12th February 2020) - Puls, Miriam; Beuthner, Bo Eric; Topci, Rodi; Vogelgesang, Anja; Bleckmann, Annalen; Sitte, Maren; Lange, Torben; Backhaus, Sören Jan; Schuster, Andreas; Seidler, Tim; Kutschka, Ingo; Toischer, Karl; et al.
Abstract: Aims : Myocardial fibrosis (MF) might represent a key player in pathophysiology of heart failure in aortic stenosis (AS). We aimed to assess its impact on left ventricular (LV) remodelling, recovery, and mortality after transcatheter aortic valve implantation (TAVI) in different AS subtypes. Methods and results : One hundred patients with severe AS were prospectively characterized clinically and echocardiographically at baseline (BL), 6 months, 1 year, and 2 years following TAVI. Left ventricular biopsies were harvested after valve deployment. Myocardial fibrosis was assessed after Masson's trichrome staining, and fibrotic area was calculated as percentage of total tissue area. Patients were stratified according to MF above (MF+) or below (MF−) median percentage MF (≥11% or <11%). Myocardial fibrosis burden differed significantly between AS subtypes, with highest levels in low ejection fraction (EF), low-gradient AS and lowest levels in normal EF, high-gradient AS (29.5 ± 26.4% vs. 13.5 ± 16.1%, P = 0.003). In the entire cohort, MF+ was significantly associated with poorer LV function, higher extent of pathological LV remodelling, and more pronounced clinical heart failure at BL. After TAVI, MF+ was associated with a delay in normalization of LV geometry and function but not per se with absence of reverse remodelling and clinical improvement. However, 22 patients died during follow-up (mean, 11 months), and 14 deaths were classified as cardiovascular (CV) ( n = 9 arrhythmia-associated). Importantly, 13 of 14 CV deaths occurred in MF+ patients (CV mortality 26.5% in MF+ vs. 2% in MF− patients, P = 0.0003). Multivariate analysis identified MF+ as independent predictor of CV mortality [hazard ratio (HR) 27.4 (2.0–369), P = 0.01]. Conclusion : Histological MF is associated with AS-related pathological LV remodelling and independently predicts CV mortality after TAVI.